2021
DOI: 10.48550/arxiv.2112.05472
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nucleation at finite temperature: a gauge-invariant, perturbative framework

Abstract: We present a gauge-invariant framework for bubble nucleation in theories with radiative symmetry breaking at high temperature. As a procedure, this perturbative framework establishes a practical, gauge-invariant computation of the leading order nucleation rate, based on a consistent power counting in the high-temperature expansion. In model building and particle phenomenology, this framework has applications such as the computation of the bubble nucleation temperature and the rate for electroweak baryogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 46 publications
(76 reference statements)
1
30
0
Order By: Relevance
“…Further, it has been demonstrated that one must include two-loop thermal effects to achieve better than O(1) numerical accuracy [664][665][666][667]. The thermodynamic quantity with largest uncertainty is presently the bubble nucleation rate, as it involves both spacetime dependence and near equilibrium physics, though recent work has improved its determination [668][669][670][671][672].…”
Section: [Contributor(s): Brian Shuve and Jessica Turner]mentioning
confidence: 99%
“…Further, it has been demonstrated that one must include two-loop thermal effects to achieve better than O(1) numerical accuracy [664][665][666][667]. The thermodynamic quantity with largest uncertainty is presently the bubble nucleation rate, as it involves both spacetime dependence and near equilibrium physics, though recent work has improved its determination [668][669][670][671][672].…”
Section: [Contributor(s): Brian Shuve and Jessica Turner]mentioning
confidence: 99%
“…Its profile for T T c is important for the purpose. However, the locations of the extrema of V T , as well as the ratio φ c (T c )/T c , are both gauge-dependent [65, 96-100] 3 see, for example, references [90,[101][102][103][104]. We have checked the minimization of V T using both Landau and Feynman gauges and have found that the gauge-dependencies of both φ c (T c ) and T c are not significant for the benchmark scenarios we present.…”
Section: Effective Higgs Potential At Finite-temperaturementioning
confidence: 99%
“…With upcoming gravitational wave detectors like LISA offering enhanced observational prospects for cosmological gravitational wave backgrounds, there have been increased efforts to understand first-order phase transitions in precise detail. Recent years have seen advances in the determination of the asymptotic wall speed for expanding bubbles [8][9][10][11][12][13][14][15][16], more precise calculations of the thermodynamic phase transition parameters and nucleation rates [17][18][19][20][21][22][23][24][25][26], and refined baryogenesis computations [27][28][29][30][31]. Holographic techniques have been used to compute phase transition parameters and gravitational wave signals [12,16,[32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%